From Good Knowers to Just Knowers in the Mahãbhãrata : Towards a Comparative Virtue Epistemology. (30th June 2014) - Dalmiya, Vrinda
Abstract Adopting the framework of Anglo Analytic Virtue Epistemology, I ask of the Sanskrit epic, the Mahābhārata, the question: What sort of character or 'intellectual virtues' must a 'good knower' have? Then, inspired by broadly feminist sensibilities, I raise the concern whether dispositions for knowing the world can be associated with motivations to rectify injustices in that world – whether, in other words, a good knower is also a 'just knower.' I go on to explore the structure of humility and shame as 'virtues of truth' in the epic to see whether they can establish a connection between knowing and justice.